2022
DOI: 10.3390/nu14132570
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Risk Factors Associated with Iodine Deficiency in Canadian Adults

Abstract: Iodine is a trace micronutrient that is critical for normal thyroid function and human health. Inadequate dietary intake is associated with cognitive impairment, infertility, growth retardation and iodine deficiency disorders in affected populations. Herein, we examined the prevalence of iodine deficiency in adults (median age of 61 years) based on the analysis of 24 h urine samples collected from 800 participants in four clinical sites across Canada in the Prospective Urban and Rural Epidemiological (PURE) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
1
0
1
Order By: Relevance
“…According to several systematic reviews and meta-analyses, females were found highly likely to develop iodine deficiency compared to males [ 20 , 21 ]. Regarding the other main factor, goitrogenic food consumption, studies conducted elsewhere showed that the burden of iodine deficiency is significantly higher among those who consume goitrogenic foods compared to those who never consumed it [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to several systematic reviews and meta-analyses, females were found highly likely to develop iodine deficiency compared to males [ 20 , 21 ]. Regarding the other main factor, goitrogenic food consumption, studies conducted elsewhere showed that the burden of iodine deficiency is significantly higher among those who consume goitrogenic foods compared to those who never consumed it [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Além de fatores relacionados ao consumo alimentar, como utilização ou não de sal iodado, temperos caseiros e industrializados são também associados ao estado nutricional de iodo características socioeconômicas e demográficas, uma vez que determinantes como renda, escolaridade, condições de moradia podem influenciar de forma indireta o estado nutricional de iodo, assim como hábitos e estilo de vida, a exemplo o tabagismo MATHIAPARANAM et al, 2022).…”
Section: Introductionunclassified